The China order : Centralia, world empire, and the nature of Chinese power - Wang, Fei-Ling (State University of New York Press, 2017)
"Examines the rising power of China and Chinese foreign policy through a revisionist analysis of Chinese civilization. What does the rise of China represent, and how should the international community respond? With a holistic rereading of Chinese longue durée history, Fei-Ling Wang provides a simple but powerful framework for understanding the nature of persistent and rising Chinese power and its implications for the current global order. He argues that the Chinese ideation and tradition of political governance and world order--the China Order--is based on an imperial state of Confucian-Legalism as historically exemplified by the Qin-Han polity. Claiming a Mandate of Heaven to unify and govern the whole known world or tianxia (all under heaven), the China Order dominated Eastern Eurasia as a world empire for more than two millennia, until the late nineteenth century. Since 1949, the People's Republic of China has been a reincarnated Qin-Han polity without the traditional China Order, finding itself stuck in the endless struggle against the current world order and the ever-changing Chinese society for its regime survival and security. Wang also offers new discoveries and assessments about the true golden eras of Chinese civilization, explains the great East-West divergence between China and Europe, and analyzes the China Dream that drives much of current Chinese foreign policy"--Publisher description.